Effect of organic manures on agronomic and economic performance of garden pea (Pisum sativum) and on soil properties - GOPINATH, K A; MINA, B L (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during 2005-07 at Almora, Uttarakhand to evaluate the effect of different organic manures (farmyard manure, poultry manure and vermicompost) and biofertilizers [Rhizobium leguminosarum + phosphorus-solubilizing bacteria (Pseudomonas sp.)] on yield of organically, grown garden pea [Pisum sativum subsp. hortense (Neilr.) Asch & Graebn] and on soil properties. Pod yields for all the treatments were significantly higher than the control. In both the years, application of farmyard manure 10 tonnes/ha + poultry manure and vermicompost each 1.5 tonnes/ha + biofertilizers gave the highest pod yields (7.02 and 7.52 tonnes/ha) and it was significantly superior to other treatments except farmyard manure 20 tonnes/ha + biofertilizers and application of farmyard manure 10 tonnes/ha + recommended NPK (20:26:33 kg/ha) through fertilizers. Application of farmyard manure 20 tonnes/ha + biofertilizers resulted in the lowest soil bulk density (1.19 Mg/m3) compared to other treatments. The soil pH increased in all the treatments compared to control. Similarly, soil organic C was significantly higher in all the treatments (1.21–1.30%) except in poultry manure 5 tonnes/ha + biofertilizers compared to control (1.06%). Application of farmyard manure 10 tonnes/ha + recommended NPK, however, recorded significantly higher available N than plots under organic manures. Application of farmyard manure 10 tonnes/ha + recommended NPK being at par with application of farmyard manure 10 tonnes/ha + poultry manure and vermicompost each 1.5 tonnes/ha + biofertilizers registered significantly higher available P and K contents in soil compared to other treatments. Application of farmyard manure 10 tonnes/ha + recommended NPK gave highest net returns (` 63 295 /ha) compared to other treatments. However, all organic treatments except vermicompost 7.5 tonnes/ha + biofertilizers gave higher net returns (` 64 148 – 75 498/ha) than application of farmyard manure 10 tonnes/ha + recommended NPK, when a price premium (10–15%) was assigned to organic garden pea.